The Treatment Outcomes of Tuberculosis Patients at Adare General Hospital, Southern Ethiopia (A Five-Year Retrospective Study) - Bizunesh Tsegaye; Zufan Bedewi; Solomon Asnake (Tropical Medicine and Infectious Disease)
Ethiopia is among the countries most heavily affected by tuberculosis, where it is the leading cause of morbidity, the third cause of hospital admission and the second cause of death. To improve tuberculosis management and control, the early detection of cases, effective treatment and the persistent evaluation of treatment outcomes are vital issues that should be taken into consideration. This study was designed to determine the treatment outcomes and associated risk factors among TB patients registered at Adare General Hospital in Southern Ethiopia. A five-year retrospective study was conducted by reviewing the files of the TB patients registered from September 2013 to August 2017. The data were coded, cleaned, entered and analyzed using SPSS version 20 statistical software. Bivariate and multivariable logistic regression with odds ratios (OR) along with a 95% confidence interval was computed and interpreted. A p-value < 0.05 was declared as statistically significant. Among the 1122 cases, 620 (55.3%) were male, 748 (66.7%) were from urban areas, 319 (28.4%) were smear positive, 352 (31.4%) were smear negative and 451 (40.2%) were extra-pulmonary patients. Among the treated patients, 284 were declared cured, 753 completed their treatment, 29 were defaulters, 3 failed to follow up, and 53 died. The overall treatment success rate was 92.4%. The TB patients from urban areas (AOR = 1.44, 95% CI: 0.28, 0.67), and the HIV-negative TB patients (AOR = 5.48, 95% CI; 3.474, 8.64) were significantly associated with successful treatment outcomes. The treatment success rates of tuberculosis at Adare General Hospital were comparable to the national health facility-level coverage, but they should be maintained and strengthened further to attain tuberculosis-related national and millennium goals.